Analisis Implementasi Pembelajaran Luring Menjadi Daring Saat Pandemi Covid-19 Pada Mahasiswa Pendidikan Ekonomi Universitas Ekasakti - Dessyta Gumanti; Serli Diovani Teza; Reni Respita (Universitas Negeri Surabaya, 2022)
This study attempts to evaluate how Ekasakti University's Economic Education students used offline learning to become online during the covid-19 pandemic. This research employs a descriptive research design with a qualitative methodology. The primary and secondary data sources for this study are primary and secondary data. The subject of this study is a student in Ekasakti University's Economic Education Study Program who participated in online learning during the covid-19 epidemic. Interactive analysis was used in the data analysis technique. The results showed that the overall implementation of learning from offline to online for Economic Education students at Ekasakti University went well during the covid-19 pandemic, but there were several obstacles encountered in general, including the readiness to access the internet, namely difficult internet networks and expensive internet quotas, and difficulties in understanding the material, with the problem encountered specifically in using the Digital Class Platform.